Infusion of ex-vivo expanded human TCR-αβ+ double-negative regulatory T cells delays onset of xenogeneic graft-versus-host disease. (31st July 2018) - Achita, P; Dervovic, D; Ly, D; Lee, J B; Haug, T; Joe, B; Hirano, N; Zhang, L
Summary: Despite the demonstration of potent immunosuppressive function of T cell receptor (TCR)-αβ + double-negative regulatory T cells (DN Tregs ), scarce numbers and lack of effective expansion method limit their clinical applications. Here we describe an approach that allows for ∼3500-fold ex-vivo expansion of human DN Tregs within 3 weeks with > 97% purity. Ex-vivo -expanded DN Tregs suppress proliferation of polyclonally stimulated autologous T and B cells in vitro through direct cell-to-cell contact. In vivo, we demonstrate for the first time that infusion of human DN Tregs delayed an onset of xenogeneic graft- versus -host disease (GVHD) significantly in a humanized mouse model. Furthermore, preincubation of ex-vivo -expanded DN Tregs with a mechanistic target of rapamycin (mTOR) inhibitor rapamycin enhanced their immune regulatory function further. Taken together, this study demonstrates that human DN Tregs can be expanded ex vivo to therapeutic numbers. The expanded DN Tregs can suppress proliferation of T and B cells and attenuate GVHD, highlighting the potential clinical use of DN Tregs to mitigate GVHD. Graphical Abstract: